2020
DOI: 10.1111/jfpp.14687
|View full text |Cite
|
Sign up to set email alerts
|

Male date palm flower powder: Effect of incorporation on physico‐chemical, textural, and sensory quality of biscuits

Abstract: This study aims to elucidate the effect of male date palm flower (MDPF) incorporation in the dough properties and biscuit characteristics. Farinograph analysis demonstrated a progressive increase in water absorption (56.85%–61%) and dough stability (1.88–20.25 min) with increasing MDPF quantity due to its wealth in dietary fiber. Biscuit formulations were prepared using 3, 6, and 9% MDPF powder and evaluated for their physico‐chemical, textural, and sensory properties. The results have shown a significant incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The findings of this investigation align with the findings of Karra et al [71], who explained that the results of the physical properties of biscuits fortified with date powder were in different percentages (3, 6, and 9%). Increasing the percentage of wheat flour replaced with tamer powder caused an increase in the spread ratio.…”
Section: Physical Propertiessupporting
confidence: 91%
“…The findings of this investigation align with the findings of Karra et al [71], who explained that the results of the physical properties of biscuits fortified with date powder were in different percentages (3, 6, and 9%). Increasing the percentage of wheat flour replaced with tamer powder caused an increase in the spread ratio.…”
Section: Physical Propertiessupporting
confidence: 91%
“…This introduction has been tested by direct insertion of intact various floral parts (petals, stems, sepals) or by incorporating their extracts or essential oils [21]. Currently, there are several studies that report the functionality of flower phytochemicals when applied in different food formulations, namely in dairy products such as yogurt [22][23][24][25], ice cream [26], or pastry products [27][28][29].…”
Section: Chemical Composition Of Edible Flowersmentioning
confidence: 99%
“…These agro resources have been widely used for production of a tonic drink with antidiabetic and antioxidant effects. Although male date palm flowers are rich in proteins (14.8%) and then constitute available agro resources that can be valorized, it was not described until now as a protease inhibitor source . In this context, the current study reported the purification and biochemical characterization of a new serine protease inhibitor named PIDF from date palm flowers P.…”
Section: Introductionmentioning
confidence: 98%
“… 7 Separate plants with unisexual inflorescences of staminate or pistillate flowers called “male and female” palms, respectively, characterize this dioecious species. 8 Recently, Karra et al 9 reported that male date palms provide about 1575 tonnes/year of flowers in Tunisia. These agro resources have been widely used for production of a tonic drink with antidiabetic and antioxidant effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation